Relation of postoperative pain medication to return for unplanned care after ureteroscopy. Issue 2 (3rd April 2019) - Milburn, Preston A.; Thai, Kim H.; El Mekresh, Amr; Lowry, Patrick S.; El Tayeb, Marawan M.
Abstract: To determine whether the US Drug Enforcement Agency (DEA) class of narcotics prescribed to patients after ureteroscopy impacts their rate of return for unplanned care, a retrospective analysis of patients from February 2014 through March 2016 was performed. Data were collected for the first 90 days after surgery. Patients were divided into groups based on the narcotics schedule prescribed after surgery. Results showed that there was no statistical difference in return for unplanned care when comparing the groups based on their prescribed pain medication. Among the 475 patients, 17% returned to the emergency department after ureteroscopy, 12% contacted the clinic due to discomfort/pain, and 8% were readmitted to the hospital within 90 days of surgery. The data indicated that patients who were not prescribed a narcotic after surgery sought unplanned care at a slightly higher rate than those who were. In conclusion, the US DEA class of narcotics prescribed after ureteroscopy did not have a statistically significant impact on the rate of return for unplanned care. These findings may improve opioid stewardship in patients undergoing outpatient ureteroscopy.